Co to jest tekst precedensowy? - Gos, Elżbieta (Przegląd Rusycystyczny, 2006)
WHAT IS A PRECEDENT TEXT? Summary The paper deals with some aspects of the precedent texts studying — a defi nition of these texts, intertextual, cognitive, pragmatic and lingua-cultural aspects. О ПОНЯТИИ ПРЕЦЕДЕНТНОГО ТЕКСТА Резюме В статье говорится о понятии прецедентного текста и некоторых аспектах его исследования: интертекстуальном, когнитивном, прагматическом и лингвокультурологическом.